ANALISIS PROSEDUR PEMBERIAN KREDIT PADA DUIT RIMBAK GINTONG DI DESA SETAWAR - Libertus, Libertus; Asriati, Nuraini; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to determine the procedure for granting credit at Duit Rimbak Gintong in Setawar Village. The research approach used in this research is descriptive qualitative research. The informants in this study were 3 representatives of the Duit Rimbak Gintong organization. The data collection technique was to conduct observations, interviews, and documentation. The results of the study are: (1) The requirements that must be met are KTP; (2) the submission mechanism is to come directly to the Duit Rimbak Gintong management; (3) the application can only be approved by the Duit Rimbak Gintong core management; (4) there is no special agreement and customers are charged 10% interest on loans; (5) there is no supervision of creditors; (6) the repayment system can be paid in installments and paid directly. (7) As of July 2024, bad debts reached RP 46.532.000.00. Duit Rimbak Gintong is a financial institution established based on the results of the RT 04 Gintong village management meeting, which is engaged in managing village treasury money, and the money can be loaned by the community on interest-bearing terms. The procedure for granting credit at Duit Rimbak Gintong in Setawar Village in serving credit granting services is not at all close to the general standards of credit granting procedures that apply.